Her Venetian secret - Crews, Caitlin (Harlequin presents, 2024)
"Cinderella's night in Venice...and her nine-month surprise. Prim headmistress Beatrice hides her true self behind strict behavior and a stricter dress code. Until she abandons her usual disguise and allows herself one intoxicating night with a stranger! Except now she's hiding the biggest secret of all...When Beatrice is hired by billionaire Cesare Chiavari to mind his half sister for the summer, she accepts. Only to discover when she arrives at the palazzo that he's the mysterious Italian she shared one passionate night with! Worse still, while the heat between them still lingers, Cesare doesn't recognize her at all..."-- back cover.